M6A Reader YTHDF1‐Targeting Engineered Small Extracellular Vesicles for Gastric Cancer Therapy via Epigenetic and Immune Regulation (Adv. Mater. 8/2023). Issue 8 (24th February 2023) - You, Qing; Wang, Fang; Du, Rong; Pi, Jingnan; Wang, Huayi; Huo, Yue; Liu, Jingyi; Wang, Chen; Yu, Jia; Yang, Yanlian; Zhu, Ling
Abstract : Engineered Extracellular Vesicles In article number 2204910, Jia Yu, Yanlian Yang, Ling Zhu, and co‐workers report an extracellular‐vesicle‐based nanodrug for the targeting delivery of short interfering RNA (siRNA) against N6‐methyladenosine (m6A) reader YTH N 6 ‐methyladenosine RNA binding protein 1 (YTHDF1) for the epigenetic and immune regulation of gastric cancer. This versatile nanoplatform provides an efficient and low toxic strategy to inhibit epigenetic regulators and holds great potential in promoting immunotherapy.